Association Between Human Gut Microbiome and N-Glycan Composition of Total Plasma Proteome - Petrov, Vyacheslav A.; Sharapov, Sodbo Zh.; Shagam, Lev; Nostaeva, Arina V.; Pezer, Marija; Li, Dalin; Hanić, Maja; McGovern, Dermot; Louis, Edouard; Rahmouni, Souad; Lauc, Gordan; Georges, Michel; et al. (Frontiers in Microbiology, 2022)
Being one of the most dynamic entities in the human body, glycosylation of proteins fine-tunes the activity of organismal machinery, including the immune system, and mediates interaction with the human microbial consortium, typically represented by the gut microbiome. Using data from 194 healthy people, we conducted an associational study to uncover potential relations between gut microbiome and blood plasma N-glycome, including N-glycome of immunoglobulin G. While lacking strong linkages on the multivariate level, we were able to identify associations between alpha and beta microbiome diversity and blood plasma N-glycome profile. Moreover, for two bacterial genera, Bilophila and Clostridium innocuum group, significant associations with specific glycans were also shown. Our results suggest a non-trivial, possibly weak link between total plasma N-glycome and gut microbiome, predominantly involving glycans related to the immune system proteins, including immunoglobulin G. Lager studies of glycans linked to microbiome-related proteins in well-selected patient groups are required to conclusively establish specific associations.